﻿Raw material "Trifolii pratense herba" originated from southern Ukraine: diagnostic microscopic features and its antioxidant activity - Olena Grechana; Inna Shevchenko; Anna Rudnik; Olena Saliy; Larysa Fukleva; Anatoly Serbin (Pensoft Publishers, 2022)
As a result of pharmacognostic and pharmacological studies, diagnostic signs of Trifolii pratense grass collected in the phenophase of active flowering in the area of southern Ukraine were revealed. We have proposed the adoption of an appendix to the existing monograph of the State Service of Ukraine on Medicines and Drugs Control "Trifolii inflorescences", with raw material of grass Trifolii pratense, with appropriate microscopic identification of diagnostic signs of leaves and stems of the plant. According to our previously found optimal conditions for extraction of medicinal plant raw materials (ratio of solvent-plant material, time and temperature of extraction), selected aqueous extract (1: 5) of clover grass with yields of maximum active substances to the extract from 60 min to 24 hours, which showed lower values of TBARS (0.541 ± 0.0291 μM / g, mean ± SD), which gives grounds to recommend the use of raw materials as an antioxidant, compared with the action of ascorbic acid.